LibQUAL+ in the local context: results, action and evaluation. Presented at the 6th Northumbria International Conference on Performance Measurement in Libraries and Information Services, Durham, 22–25 August, 2005 - Lock, Selena A.; Town, J. Stephen (Cranfield University, 2005)
This paper discusses the use of the LibQUAL+ library survey instrument and its ability to define an agenda for further improvements in a setting where quality maturity is high and library performance tends to be generally acknowledged as good. The results from the survey run in 2003 and 2005 are presented, and how these results have been used to form a change agenda discussed. In particular the indications of the effect of improvement projects across the years are described. The revelation of differing perceptions of library staff and users to the service is described, and the approaches taken to close this gap through more effective internal marketing and communication are discussed. Comparisons of the LibQUAL+ results with an internal exit questionnaire are also presented. Conclusions about the benefit of the use of the LibQUAL+ survey instrument within a local context of quality are drawn.
Keywords: LibQUAL+; performance measurement; user surveys; library service quality